Mitochondrial complex IV mutation increases reactive oxygen species production and reduces lifespan in aged mice. (20th November 2018) - Reichart, Gesine; Mayer, Johannes; Zehm, Cindy; Kirschstein, Timo; Tokay, Tursonjan; Lange, Falko; Baltrusch, Simone; Tiedge, Markus; Fuellen, Georg; Ibrahim, Saleh; Köhling, Rüdiger
Abstract: Aim: Mitochondrial DNA (mtDNA) mutations can negatively influence lifespan and organ function. More than 250 pathogenic mtDNA mutations are known, often involving neurological symptoms. Major neurodegenerative diseases share key etiopathogenetic components ie mtDNA mutations, mitochondrial dysfunction and oxidative stress. Methods: Here, we characterized a conplastic mouse strain (C57BL/6 J‐mtNOD) carrying an electron transport chain complex IV mutation that leads to an altered cytochrome c oxidase subunit III. Since this mouse also harbours adenine insertions in the mitochondrial tRNA for arginine, we chose the C57BL/6 J‐mtMRL as control strain which also carries a heteroplasmic stretch of adenine repetitions in this tRNA isoform. Results: Using MitoSOX fluorescence, we observed an elevated mitochondrial superoxide production and a reduced gene expression of superoxide dismutase 2 in the 24‐month‐old mtNOD mouse as compared to control. Together with the decreased expression of the fission‐relevant gene Fis1, these data confirmed that the ageing mtNOD mouse had a mitochondrial dysfunctional phenotype. On the functional level, we could not detect significant differences in synaptic long‐term potentiation, but found a markedly poor physical constitution to perform the Morris water maze task at the age of 24 months. Moreover, the median lifespan of mtNOD mice was significantly shorter than of control animals. Conclusion: Our findings demonstrate that a complex IV mutation leads to mitochondrial dysfunction that translates into survival.